PENGARUH PELAYANAN, MOTIVASI KERJA, KOMITMEN ORGANISASI, DAN BUDAYA ORGANISASI TERHADAP KINERJA MANAJERIAL PDAM TIRTA INDRAGIRI KOTA TEMBILAHAN, PDAM TIRTA KAMPAR KOTA BANGKINANG, DAN PDAM TIRTA SIAK KOTA PEKANBARU - Pratiwi, Nony Indah; Desmiyawati d, Desmiyawati; Putra, Adhitya Agri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research aims to analyze about (1) the influence of services on managerial performance, (2) the influence of work motivation on managerial performance, (3) the influence of organizational commitment on managerial performance, (4) the influence of organizational culture on managerial performance.This research was conducted at PDAM Tirta Indragiri Tembilahan City, PDAM Tirta Bangkinang Kampar City, and PDAM Tirta Siak Perkanbaru City in 2018. The sample used as the respondent taken using puposive method of sampling. The number of samples in this research as much as 50 respondents. Hypothesis testing in the research was carried out using statistical tests t. Technical analysis of the data used in this study is the analysis of multiple linear regression (Multiple Linear Regression) using a software program of data processing Statistical Product and Service Solution (SPSS) version 24.0 for windows. The results of this study indicate that the variable service, work motivation, organizational commitment, and organizational culture affect managerial performance variables. From the result of determination coefficient test show the influence of service variable, work motivation, organizational commitment, and organizational culture have an effect on managerial performance variable equal to 61%, while the rest 39% influenced by other variable not included in this research.Keywords : Service, Work Motivation, Organizational Commitment, Organizational Culture, Managerial Performance